Prevalência de Cryptosporidium sp. em cães de instituições da cidade de São Paulo - Lallo, M. A.; Bondan, E. F. (Revista de Saúde Publica, 2006)
Objective Dogs play an important role as infection source of human cryptosporidiosis. The objective of the study was to determine the prevalence of Cryptosporidium sp. in dogs as well as to compare two techniques of fecal analysis.Methods Four-hundred and fifty canine fecal samples from the city of São Paulo were analyzed between 2003 and 2004. Fecal samples were randomly selected from dogs housed in a university veterinary hospital (group 1, n=200) and private kennels (group 2, n=250). The detection of Cryptosporidium was performed using modified Ziehl-Neelsen staining and Polymerase Chain Reaction (PCR) technique. Statistical analysis was performed using the two-tailed test of significance at 5% confidence interval (z critical=+/- 1.645).Results Only Cryptosporidium parvum oocysts were found the prevalences found by light microscopy examination and PCR techniques were 8.8% and 9.5%, respectively. Young animals showed a lower frequency (5.5%) compared to adults (10.1%). There was no statistically significant difference in Cryptosporidium prevalence between males and females.Conclusions the prevalence of C. parvum in the canine population studied was similar to that one found in the literature and affects equally males and females. The use of PCR allowed the detection of more positive cases than light microscopy.
Prevalence of Cryptosporidium sp in institutionalized dogs in the city of São Paulo, Brazil
Keywords: Cryptosporidium, isolation & purification; prevalence; dogs; Feces; parasitology; polymerase chain reaction